Factors accounting for low patronage of handicrafts, among tourists in Osogbo, Osun State / Tijani, N.O. ...[et al.] - Tijani, N.O; Ogundele, A.; Yina, Orga Donald (Universiti Teknologi MARA (UiTM), Malaysia, 2012)
This study examines the low patronage of handcraft among tourists in Osogbo with a view to know the4 problems they are encountering as well as suggest appropriate strategies to improve the level of patronage- participatory approach entail interview, discussion and focus group discussion were used to collect data on the subject of study. Data's were collected from both the handicraft producers and the tourists it was discovered that the major problems accounting for low patronage of handicrafts are low quality of product, poor design, and expensiveness of the product, communication gap, and lack of usefulness of the product among others. It was recommended that the government should undertake major investment in handicraft sector and strengthen capacity building in the sector overcome critical problems associated with quality, design and usefulness of the product.